JUAL BELI E-COMMERCE DALAM PERSFEKTIF HUKUM ISLAM - Hidayah, Ardiana (Solusi, 2019)
Buying and selling is one type of mu'amalah regulated in Islamic Law. Based on its form, e-commerce is a model of buying and selling transactions. The concept of e-commerce buying and selling leads to engagement between the parties to provide an achievement. Based on Sunnah Fiqh, buying and selling is the exchange of property (whatever its form) is done voluntarily or the process of transferring property rights to other people with compensation or certain rewards. According to Islamic Law, e-commerce buying and selling is permissible, if it is in accordance with the rules of fiqh in the basic principles of muamalah transaction and its requirements as long as it is not prohibited by sharia or contrary to the argument